2022
DOI: 10.7181/acfs.2021.00479
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of temporal hollowing deformities using silicone implants made using a toy-clay model: a report of three cases

Abstract: Severe temporal hollowing deformities can occur in patients who undergo craniectomy after intracranial hemorrhage. Reconstruction surgery for cosmetic purposes using silicone implants in patients with temporal hollowing deformities after craniectomy is advantageous because the procedure is simple and rapid, with a short recovery time, resulting in lower overall treatment costs. Of paramount importance, this option yields highly satisfactory results for patients. The authors present three cases of simple and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Various methods are used to reconstruct temporal hollowing with alloplastic materials, such as poly-methyl-methacrylate, hydroxyapatite, and polyetheretherketone [7]. This type of correction can be performed without donor site morbidity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Various methods are used to reconstruct temporal hollowing with alloplastic materials, such as poly-methyl-methacrylate, hydroxyapatite, and polyetheretherketone [7]. This type of correction can be performed without donor site morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Another traditional method of reconstruction uses autologous tissue (e.g., bone grafts, dermofat grafts, and fat grafts). However, donor site morbidity, inadequate engraftment, and limitations of the volume of harvested tissue can be problematic [7]. Because reconstruction for temporal hollowing is performed near scar tissue from a previous operation, the survival rate of the autologous graft can be affected by a hostile tissue environment [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Park et al [9] suggested a method of placing the three-dimensional (3D) printed implant between the superficial and deep layers of the temporalis muscle to improve esthetic outcomes in 2019. Kim et al [10] reported three cases of satisfying outcomes using silicone implants made with a toy-clay model. We suggest a simple suture sling technique to help resolve this problem.…”
Section: Introductionmentioning
confidence: 99%